2021
DOI: 10.3389/fmolb.2021.568818
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Prognostic Value of Methylated Septin9 and its Association With Clinicopathological and Molecular Characteristics in Colorectal Cancer

Abstract: Screening of CRC continues to show poor compliance of endoscopy examination. The detection of mSEPT9 in peripheral blood is among the safe and simple early screening methods for CRC. The issue of how to elucidate whether detection of mSEPT9 in peripheral blood can effectively improve compliance of endoscopy and increase the early diagnosis rate of CRC and the relationship between levels of mSEPT9 in the peripheral blood and clinical stage, pathological classification, and expression of characteristic molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…In our study, 94 CRC patients in stage II and III were analyzed by combining mSEPT9. 38.3% of patients underwent local recurrence or distant metastasis at the 2-year follow-up, consistent with the previous report [ 23 ]. Our results confirmed that mSEPT9 was an independent prognosis marker for CRC patients in stage II and III.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, 94 CRC patients in stage II and III were analyzed by combining mSEPT9. 38.3% of patients underwent local recurrence or distant metastasis at the 2-year follow-up, consistent with the previous report [ 23 ]. Our results confirmed that mSEPT9 was an independent prognosis marker for CRC patients in stage II and III.…”
Section: Discussionsupporting
confidence: 90%
“…Based on mSEPT9, stage II and III patients could be further classified to provide a basis for individualized adjuvant therapy. Previous studies only simply found that the status of mSEPT9 before surgery was associated with survival of CRC patients [ 22 , 23 ], lacked in-depth understanding of its specific role. We stratified stage II and III patients in detail using mSEPT9 and clearly demonstrated the role of mSEPT9 in survival outcomes for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have generally reported a 2‐ to 3‐fold increase in risk of recurrence. There are other studies reporting on the prognostic value of methylation‐based detection of ctDNA but their estimates arose from testing before commencing treatment 46,47 …”
Section: Discussionmentioning
confidence: 99%
“…There are other studies reporting on the prognostic value of methylation-based detection of ctDNA but their estimates arose from testing before commencing treatment. 46,47 At this point in time, there is no gold-standard for diagnosing the presence of minimal residual disease (MRD) and we are dependent on subsequent clinical course to identify those cases where disease has not been eradicated. There is a considerable amount of literature reporting the utility of somatic mutation-and/or epigenetic-based detection of ctDNA after surgical resection to identify those patients might benefit the most from adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have shown that mSEPT9 represents a promising biomarker for CRC detection. Studies have shown that the rate of SEPT9 methylation in peripheral blood of patients with CRC is related to clinicopathological features; for example, SEPT9 methylation is positively correlated with the malignancy of CRC [11][12][13]. After radical resection of colorectal cancer, the level of mSEPT9 in peripheral blood decreases; however, the level increases after recurrence, suggesting that mSEPT9 in peripheral blood can be used for evaluating the pathological stages of CRC and may represent a molecular biological indicator for evaluating prognosis, recurrence, and metastasis [14,15].…”
Section: Introductionmentioning
confidence: 99%